MULTIPLE ORGAN FAILURE IN PEDIATRIC CRITICAL CARE: ADVANCES IN PATHOPHYSIOLOGY AND PROGNOSIS - EVGENIYA O. Petrova; EVGENIY V. Grigoriev (Фундаментальная и клиническая медицина)
Multiple organ failure is a leading cause of admission to the intensive care units, characterized by a high case fatality rate and significant financial costs. Here we review the mechanisms of multiple organ failure in pediatric patients (triggers, concomitant diseases, release of danger- and pathogen-associated molecular patterns, bacterial translocation, epithelial, endothelial, or mitochondrial dysfunction, and inadequate immune response) and recent diagnostic and prognostic scales.